The Additive Effect of Rosmarinic Acid for The Reduction of Glomerular NF-kB Expression in Diabetes Rat that was given Telmisartan - Mochamad Fachrureza; Nur Samsu; Achmad Rudijanto (Jurnal Penyakit Dalam Indonesia)
Introduction. Diabetic nephropathy is one of the common complications of diabetes, which one of its causes is the increase of free radicals through the activation of NF-kβ and Angiotensin II. Rosmarinic acid has the activity as the anti-oxidant and anti-inflammatory, and the telmisartan is the partial PPAR-γ agonist that has the anti-fibrotic effect. This study aimed to identify the effect of rosmarinic acid and telmisartan in the reduction of subunit p65 NF-kB expression on the glomerular diabetes rat.